2022
DOI: 10.3389/fbioe.2022.823619
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model Based on mRNA Expression Analysis of Esophageal Squamous Cell Carcinoma

Abstract: Background: The aim of this study was to identify prognostic markers for esophageal squamous cell carcinoma (ESCC) and build an effective prognostic nomogram for ESCC.Methods: A total of 365 patients with ESCC from three medical centers were divided into four cohorts. In the discovery phase of the study, we analyzed transcriptional data from 179 cancer tissue samples and identified nine marker genes using edgeR and rbsurv packages. In the training phase, penalized Cox regression was used to select the best mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Nine of these genes (HSPA6, SP100A12, CACYBP, NOS2, DKK1, DSM, STC2, NGPTL3 and NRF2) defined two ESCC subgroups: a high-risk subgroup with the enrichment of M0 and M2 macrophages and activated mast cells and a low-risk subgroup rich in CD8 T cells and regulatory T cells [51]. A recent study showed that the expression level of two genes may help define the prognosis of ESCC patients: ESCC patients with high PDZK1P1 expression had worse prognoses than those with low expression; in contrast, TM9SF1 expression levels were correlated with better prognoses [52]. The incorporation of the mRNA expression levels of these two genes with TMN staging and age allowed for the development of a prognostic model with good predictive accuracy for ESCC patients [52].…”
Section: Gene Expression Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine of these genes (HSPA6, SP100A12, CACYBP, NOS2, DKK1, DSM, STC2, NGPTL3 and NRF2) defined two ESCC subgroups: a high-risk subgroup with the enrichment of M0 and M2 macrophages and activated mast cells and a low-risk subgroup rich in CD8 T cells and regulatory T cells [51]. A recent study showed that the expression level of two genes may help define the prognosis of ESCC patients: ESCC patients with high PDZK1P1 expression had worse prognoses than those with low expression; in contrast, TM9SF1 expression levels were correlated with better prognoses [52]. The incorporation of the mRNA expression levels of these two genes with TMN staging and age allowed for the development of a prognostic model with good predictive accuracy for ESCC patients [52].…”
Section: Gene Expression Studiesmentioning
confidence: 99%
“…A recent study showed that the expression level of two genes may help define the prognosis of ESCC patients: ESCC patients with high PDZK1P1 expression had worse prognoses than those with low expression; in contrast, TM9SF1 expression levels were correlated with better prognoses [52]. The incorporation of the mRNA expression levels of these two genes with TMN staging and age allowed for the development of a prognostic model with good predictive accuracy for ESCC patients [52].…”
Section: Gene Expression Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to BC, TM9SF1 has been found to be overexpressed in esophageal and cervical cancer with a speculated link to poorer survival and recurrence rates in some preclinical studies[ 14 , 15 ]. Its role as an oncogene might be due to its effects on the G1 phase.…”
Section: Introductionmentioning
confidence: 99%
“…By establishing an effective prognostic nomogram model for esophageal squamous cell carcinoma, two marker genes were identified that are directly associated with 4-year overall survival of cancer patients, one of which is TM9SF1. The expression value of TM9SF1 gene in cancer patients was found to be significantly higher than that of healthy individuals[ 11 ]. ApostolosZaravinos’ study employed enome-wide microarray analysis, classifying samples based on histology and discovering 17 differentially expressed genes, one of which was TM9SF1.…”
Section: Introductionmentioning
confidence: 99%